حضرت مخدوم جہانیاں جہاں گشت کی علمی خدمات: ایک تحقیقی مطالعہ: THE SCHOLARLY CONTRIBUTIONS OF HAZRAT MAKHDOOM JAHANIYAN JAHANGASHT: A RESEARCH STUDY (PAKISTAN ISLAMICUS (An International Journal of Islamic & Social Sciences), 2024)
This Paper explores the intellectual and spiritual legacy of Hazrat Makhdoom Jahaniyan Jahangasht, a prominent Sufi scholar of his time. His life was marked by unwavering dedication to guiding others, blending Sharia and Tariqat (spiritual path) into a cohesive framework. His hospice served as a hub for diverse visitors, including scholars, rulers, and laypeople, all seeking his wisdom.Makhdoom Jahaniyan's teachings emphasized strict adherence to Islamic law and Prophetic traditions, rejecting deviations. He resolved theological and jurisprudential queries, such as rulings on fasting and divorce, with profound insight. His works, like Siraj al-Hidaya and Khazana Jalali, elaborated on Hadith, jurisprudence, and daily ethics, including dietary benefits.He attracted disciples globally, from Shiraz to Bukhara, and upheld the superiority of the Indian subcontinent in spiritual significance. His critiques of ignorance, oppression, and hypocrisy underscored his commitment to ethical scholarship. The Paper also highlights his reverence for the Prophet’s companions and the integration of scholarly and spiritual disciplines.